Optimum Design of Amidships Section Based on Scantlings of Stiffeners - احمد غالب (Latakia University Journal -Engineering Sciences Series, 2021)
Ships are indeed complex structures and their stiffening is also sophisticated, generally composed of stiffened plates, deck plates, bottom plates, and sometimes intermediate decks, frame, bulkheads. The longitudinal strength of hull girder depends on the section modulus of amidships section. This in turn depends on the scantlings and layout of the structural members in the Amidships region. The Amidships region extends one forth length of the ship forward and aft of midship. Over this amidships region the scantlings of the structural members are kept the same. Maximum longitudinal bending moment is experienced by a hull girder within this Amidships zone. Therefore, Amidships section plays an important role from longitudinal strength point of view, at the same time it depicts the structural layout depending on the type of cargo the is going to carry. Thus different types of ships have different midship sections. There are several requirements ( such as, structural weight, structural production cost, and safe of ship) related to ship design can be solved by various alternatives. The optimization design of amidships section scantlings ( plates and stiffeners) realizes a multi- objectives such as, minimum weight, minimum production cost, and maximum moment of inertia. In this research, the optimization of Amidships section involves a number of variables such as plate thickness, scantlings of stiffeners, and number of stiffeners, was performed using a developed computer program. The Moment of inertia of the mid ship section is computed, then the hull girder ultimate strength is determined to evaluate the optimum design of a midship section scantlings, namely minimization of the structural weight and cost and maximization of moment of inertia.